2017
DOI: 10.1016/j.rasd.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Altered pre-ejection period response to social evaluative threat in adolescents with autism spectrum disorder

Abstract: Introduction The autonomic nervous system (ANS) is involved in regulating social behavior; Autism Spectrum Disorder (ASD) is characterized by alterations in social behavior and reduced physiological response to threat. We hypothesized that adolescents with ASD would show reduced ANS response to social threat. Methods Eighteen males with ASD and thirteen males with typical development (TD), ages 12 to 17, completed a social threat paradigm while wearing an impedance cardiography apparatus. We calculated pre-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Quite to the contrary, we were able to show that PEP is a parameter of high interindividual variability which is prone to large changes under the influence of mental and physical load. These results confirm and extend the findings of psychobiologists, who demonstrated individual differences in PEP response to situations of perceived stress ( 20 22 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Quite to the contrary, we were able to show that PEP is a parameter of high interindividual variability which is prone to large changes under the influence of mental and physical load. These results confirm and extend the findings of psychobiologists, who demonstrated individual differences in PEP response to situations of perceived stress ( 20 22 ).…”
Section: Discussionsupporting
confidence: 91%
“…On the contrary, works from the field of psychobiology have shown that PEP does change under stress ( 18 20 ). Moreover, the degree of PEP variation under stress seems to be highly variable between different individuals ( 21 , 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, higher baseline RSA was related to higher levels of social skills, such as faster emotion recognition, in ASD children ( Van Hecke et al, 2009 ; Bal et al, 2010 ). Furthermore, adolescent males diagnosed with ASD (ages 12–17 years) had reduced SNS activation relative to TD controls, as indicated by the lower change in the pre-ejection period (PEP) (i.e., the interval from stimulation of the left heart ventricle to the opening of the aortic valve) at the onset of a modified version of the TSST ( Edmiston et al, 2017b ). The authors suggested that the reduced arousal in response to social cues may lead to reduced attention to social stimuli and subsequently to the altered social behaviors characterizing ASD ( Edmiston et al, 2017b ).…”
Section: Autonomic Nervous System Alterations In Children and Adolescents With Autism Spectrum Disordermentioning
confidence: 99%
“…Furthermore, adolescent males diagnosed with ASD (ages 12–17 years) had reduced SNS activation relative to TD controls, as indicated by the lower change in the pre-ejection period (PEP) (i.e., the interval from stimulation of the left heart ventricle to the opening of the aortic valve) at the onset of a modified version of the TSST ( Edmiston et al, 2017b ). The authors suggested that the reduced arousal in response to social cues may lead to reduced attention to social stimuli and subsequently to the altered social behaviors characterizing ASD ( Edmiston et al, 2017b ). Nevertheless, to date, findings regarding the associations between ANS regulation and social skills in children and adolescents with ASD converge on the fact that better skills and fewer difficulties are associated with sympathetic withdrawal and parasympathetic increase during social interaction ( Neuhaus et al, 2016 ; Patriquin et al, 2019 ).…”
Section: Autonomic Nervous System Alterations In Children and Adolescents With Autism Spectrum Disordermentioning
confidence: 99%
“…Although much research has investigated a role for HPA signaling in the relationship between autism and psychopathology, this has yielded inconsistent results. There is a large body of evidence suggesting global disruptions to cortisol signaling in autism (95,(185)(186)(187)(188)(189)(190)(191)(192)(193) and independent studies have reported HPA hyperactivation (185,188,194,195) and increased stress reactivity (186,196) in ASC. A relationship between elevated evening cortisol and psychopathology in ASC has been proposed (194); altered cortisol responses were associated with GAD and social anxiety in boys with ASC (197,198), while the cortisol awakening response was reported to correlate with depression and suicidal ideation in autistic girls (199).…”
Section: Figurementioning
confidence: 99%